Decentralized biorefinery for lignocellulosic biomass: Integrating anaerobic digestion with thermochemical conversion. (February 2018) - Sawatdeenarunat, Chayanon; Nam, Hyungseok; Adhikari, Sushil; Sung, Shihwu; Khanal, Samir Kumar
Highlights: A decentralized biorefinery concept for lignocellulosic biomass was developed. The long-term anaerobic mono-digestion of lignocellulosic biomass was investigated. Digestate has lower ash content and nearly same energy content as the raw biomass. Digestate could be thermochemically converted into high density solid fuels. The produced biofuels could be exported for co-firing with coal in power plants. Abstract: Anaerobic digestion (AD) of lignocellulosic biomass i.e. Napier grass ( Pennisetum purpureum ), was investigated via a series of batch and bench-scale experiments. Two semi-continuous bench-scale horizontal bioreactors were operated in parallel for nearly 300 days, and the reactors were able to handle the organic loading rate (OLR) up to 6 kg volatile solids (VS)/m 3 -d, which was among the highest OLR reported in the literature for lignocellulosic biomass. Hemicellulose was the main structural carbohydrate of lignocellulosic biomass per unit respective mass (dry weight) basis contributing to methane production. The cellulose- and lignin-rich digestate was further examined for its bioenergy potential via torrefaction and hydrothermal carbonization, and was found to have higher mass and energy yield compared with those of raw Napier grass. The produced solid char has energy content similar to bituminous coal with low ash content. Thus, this study provided a successful integration of anaerobic digestion with thermochemical conversion representing a biorefinery concept for lignocellulosic feedstocks.